Decreased in vitro bioaccessibility of Cd and Pb in an acidic Ultisol through incorporation of crop straw-derived biochar. (15th January 2023) - Cui, Jiaqi; Yu, Yunjiang; Xiang, Mingdeng; Shi, Yangxiaoxiao; Zhang, Feng; Fang, Di; Jiang, Jun; Xu, Renkou
Abstract: Studies analyzing the in vitro bioaccessibility (BAc) of heavy metals in biochar-amended soils are currently lacking. The present study aimed to assess the metal BAc in Cd- and Pb-spiked acidic Ultisol samples treated individually with 2% ( w/w ) maize, rice, wheat, soybean, and pea straw-derived biochar. The results indicate that the Cd-BAc simulated in gastric phase (GP) decreased from 78.4% to 66.5–72.3% and the Pb-BAC decreased from 74.3% to 67.2–69.2%; however, the Cd-BAc in the intestinal phase (IP) decreased from 35.6% to 27.9–33.5% and the Pb-BAc decreased from 34.7% to 29.7–32.9% after 120 d of incubation with biochar application compared to the un-amended Ultisol. The Cd- and Pb-BAc in both GP and IP were significantly negatively correlated with soil pH, CEC, and organic carbon ( P < 0.05), which increased after biochar application. The soybean straw-derived biochar amendment has the greatest potential to decrease the BAc of Cd and Pb in the GP and IP, owing to the highest level of CEC, SOC, TC and TN among all soil samples. Moreover, the BAc was positively correlated with the exchangeable, and exchangeable + carbonate-bound Cd and Pb fractions ( P < 0.05), indicating these fractions had a dominant influence on the BAc of cationic heavy metals. Therefore, crop straw-derived biochar amendment can decrease the BAc of Cd and Pb in acidic Ultisol, and thus mitigate the health risks posed by these metals from incidental ingestion. Graphical abstract: Image 1 Highlights: Bioaccessibility of Cd and Pb in GP decreased by 7.3–15.1% and 7.0–9.6% after biochar addition. Bioaccessibility of Cd and Pb in IP decreased by 5.9–21.5% and 5.4–14.5% after biochar addition. Soil pH, CEC, and organic matter negatively correlated with bioaccessibility. Bioaccessibility positively related to exchangeable and carbonate-bound metals.